Influence of typical stabilizers on the aging behavior of EVA foils for photovoltaic applications during artificial UV-weathering. (July 2015) - Jentsch, A.; Eichhorn, K.-J.; Voit, B.
Abstract: Ethylene vinyl acetate copolymer (EVA) is the most commonly used embedding material in crystalline silicon photovoltaics. It is responsible for fixing module components, electrical isolation and protecting cells against mechanical and environmental stresses. The degradation of EVA during weathering can cause adhesion loss, the so called delamination, and yellowing of the foil, resulting in a drop of module efficiency. In order to improve the long-term stability, several stabilizers including UV-absorber, hindered amine light stabilizer and phosphite are added to the polymer. However, the exact influence of the different stabilizers on failure mechanisms has not yet been identified in detail. Therefore, different EVA foils containing variable additive formulations were exposed to artificial UV-irradiation at 50 °C. As a result, delayed EVA degradation could be observed depending on stabilizers added. On the other hand, some of the tested additives were found to be involved in delamination and yellowing processes.